Multi-objective biological mimicry optimization algorithm for WSN sensor node placement - Abidin H.Z.; Din N.M.; Radzi N.A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Algorithms; Bioinformatics; Energy utilization; Integer programming; Multiobjective optimization; Optimization; Wireless sensor networks; biological inspired; connectivity; coverage; energy; Multi objective; Sensor node placement; WSN; Sensor nodes